Intercultural and Intertextual Crossings in Sarah Howe’s Loop of Jade (2015) - Yasna Bozhkova (Sillages Critiques, 2022)
This article explores the notion of intercultural and intertextual crossing (in the combined senses of migration and intersection) in Sarah Howe’s poetry collection Loop of Jade (2015). Born in Hong Kong to a Chinese mother and British father, Howe grew up in the UK. Loop of Jade explores the experience of cultural hybridity and deracination through an intertextual poetics predicated on artifice and irony, going against the grain of a simple, unmediated confessional poetic narrative “of the origins.” After the actual experience of return paradoxically leads to a crisis of identification, intertextuality becomes an alternative route allowing Howe to approach her origins obliquely. A Borgesian epigraph – a surprising abecedary of apparently arbitrary categories of animals given in a “certain Chinese encyclopedia” – becomes a structuring device for the whole collection, announcing its project to reflect on real or imaginary cultural differences. Working through various constructions and misconceptions of Asia in the Western imagination, the poems ultimately develop a complex sense of belonging. This article argues that Howe uses a multiplicity of intertexts to create what Homi Bhabha calls an “in-between,” interstitial subjectivity, which reflects on its intercultural plurality and fragmentation, and explores the degree to which modern identity is shaped by cultural differences. It also explores the political dimensions of Howe’s use of intertextuality, denouncing China’s history of repression and censorship, as well as the violence against women and the anxiety of miscegenation in traditional culture. Finally, I also show that Howe ambivalently engages with the legacy of modernist poetry, particularly with Ezra Pound’s appropriation of Chinese culture and writing system.